Flame-retardant antistatic composite treatment method for functional workwear fabric
Patent Information
- Application Number
- CN202610875865.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-09-11
AI Technical Summary
[0004]为了解决因纺织品加工通过后整理赋予面料阻燃或防静电功能而导致阻燃与防静电性能难以在同一面料上稳定共存的问题,本申请提供功能性工装面料的阻燃防静电复合处理方法
1、由于本申请在面料表面先后构建含金属离子的膨胀型阻燃内层和生物基防静电外层,并通过共价交联将整个涂层体系锚固于纤维表面,阻燃内层中的磷氮组分与金属离子形成凝聚相协同阻燃效应,防静电外层利用壳聚糖的吸湿性和植酸根与金属离子的络合网络建立离子传导通路,因此获得阻燃与防静电功能长效共存的工装面料。
Smart Images

Figure CN122728099A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of textile processing technology, and more specifically, to a method for flame-retardant and antistatic composite treatment of functional workwear fabrics. Background Technology
[0002] Modern textile processing is widely used in three major fields: apparel, home textiles, and industrial textiles. Among them, high-speed rotor spinning and vortex spinning technologies achieve high output in a short process; shuttleless weaving, warp knitting, and weft knitting technologies can efficiently produce a variety of woven and knitted fabrics; processes such as continuous pad dyeing with reactive dyes, digital inkjet printing, and airflow dyeing improve color accuracy and pattern freedom while reducing water and chemical consumption; and finishing technologies such as functional coatings, lamination, liquid ammonia finishing, and low-temperature plasma treatment endow fabrics with high added value functions such as waterproof and breathable properties, flame retardancy, antibacterial properties, and UV resistance.
[0003] Related textile processing involves finishing processes such as impregnation with flame retardants, coating with conductive polymers, or adding hygroscopic antistatic agents to impart flame retardant or antistatic properties to fabrics. However, this step-by-step process of adding single functions results in a distinct physical interface and poor chemical compatibility between the flame retardant layer and the antistatic layer. Furthermore, halogenated flame retardants and ionic antistatic agents are prone to migration and mutual dilution in hot and humid environments, leading to insufficient adhesion of the coating system. After repeated washing and mechanical friction, the function deteriorates, making it difficult for flame retardant and antistatic properties to coexist stably on the same fabric. This restricts the long-term protective capability of workwear fabrics under complex working conditions such as oil stains, dust, and electric arcs. Summary of the Invention
[0004] To address the problem that flame retardant and antistatic properties are difficult to coexist stably on the same fabric due to the fact that finishing processes impart flame retardant or antistatic functions to textile fabrics, this application provides a method for the composite treatment of functional workwear fabrics with flame retardant and antistatic properties.
[0005] A method for flame-retardant and antistatic composite treatment of functional workwear fabrics includes the following steps: S1. The fabric base is subjected to plasma activation treatment to obtain surface-activated fabric; S2. The surface-activated fabric is alternately immersed in cationic polyelectrolyte solution and anionic polyelectrolyte solution for self-assembly. After washing with water in between, an intumescent flame-retardant polyelectrolyte inner layer containing metal ions is formed, resulting in fabric with inner layer deposition. S3. The inner layer of deposited fabric is immersed in a crosslinking agent solution to carry out a crosslinking reaction, so that the flame-retardant polyelectrolyte inner layer and the fabric fibers form a covalent bond, and a crosslinked fixed fabric is obtained. S4. The cross-linked fixed fabric is alternately immersed in cationic and anionic solutions to perform self-assembly. After washing with water in between, a bio-based antistatic outer layer is formed on the surface of the flame-retardant polyelectrolyte inner layer to obtain a composite coated fabric. S5. The composite coated fabric is pre-baked and baked in sequence to obtain the functional workwear fabric.
[0006] By adopting the above technical solution, this method constructs an intumescent flame-retardant inner layer containing metal ions and a bio-based antistatic outer layer on the fabric surface through nanoscale layer-by-layer self-assembly. The entire coating system is anchored to the fiber surface through covalent cross-linking. The phosphorus and nitrogen components in the flame-retardant inner layer form a condensed phase with metal ions to synergistically enhance the flame-retardant effect. When heated, it rapidly expands to form a dense char layer. The metal ions simultaneously catalyze the char formation reaction and enhance the integrity of the char layer. The antistatic outer layer utilizes the hygroscopic properties of chitosan and the complexation network of phytate and metal ions to establish an ion conduction pathway, enabling the fabric to have static electricity dissipation capabilities under normal conditions and retaining a certain degree of conductivity in the char layer formed during combustion, reducing the risk of static electricity accumulation in a fire environment. Both layers originate from aqueous phase self-assembly and are connected to the fibers through covalent bonds, achieving a long-term coexistence of integrated flame-retardant and antistatic functions.
[0007] Preferably, in step S1, the atmosphere for plasma activation treatment is oxygen or air, the treatment power is 50-200W, and the treatment time is 1-10min; the base fabric is a polyester-cotton blended fabric or a flame-retardant fiber fabric.
[0008] By adopting the above technical solution, plasma activation treatment introduces oxygen-containing active groups on the fiber surface without damaging the strength of the fiber itself. These polar groups improve the wettability of the fabric surface and its affinity for aqueous polyelectrolyte solutions. They also provide abundant anchor points for chemical reactions with crosslinking agent molecules in subsequent crosslinking steps, thereby forming a strong chemical bond between the polyelectrolyte coating and the matrix fiber, which fundamentally enhances the coating's durability.
[0009] Preferably, in step S2, the cationic polyelectrolyte solution is prepared by dissolving polyethyleneimine with a molecular weight of 600-750 kDa in water to prepare a solution with a concentration of 0.5-2.0 wt%, then adding zinc nitrate to make the zinc ion concentration 0.05-0.5 mol / L, and stirring to complex.
[0010] By adopting the above technical solution, the dense amine groups on the high molecular weight polyethyleneimine molecular chain are protonated under acidic to neutral conditions, giving it cationic properties and driving electrostatic alternating assembly with anionic polyelectrolytes. At the same time, it participates in the subsequent char layer construction as a nitrogen source and char-forming agent in the intumescent flame retardant system. The pre-complexed zinc ions are uniformly deposited into the coating along with the polyethyleneimine. These metal ions catalyze the phosphorylation reaction in the condensed phase, promote the dehydration and cross-linking of fiber and coating components into char, improve the flame retardant efficiency, and form an ionic cross-linked conductive network when in contact with phytic acid in the future, so that a single component can serve both flame retardant and antistatic functions.
[0011] Preferably, in step S2, the anionic polyelectrolyte solution is prepared by dissolving ammonium polyphosphate with a degree of polymerization ≥1000 in water to prepare a solution with a concentration of 1.0 to 3.0 wt%, then adding melamine as an auxiliary char-forming agent to make its concentration 0.2 to 0.8 wt%, and adjusting the pH to 5 to 7.
[0012] By adopting the above technical solution, high-polymerization-degree ammonium polyphosphate, as an inorganic acid source and phosphorus source, together with the nitrogen source provided by polyethyleneimine and the melamine-assisted foaming agent, constitutes a phosphorus-nitrogen intumescent flame retardant system. During the alternating deposition process, ammonium polyphosphate forms a uniform polyelectrolyte composite multilayer film through the electrostatic interaction between phosphate groups and the protonated amine groups of polyethyleneimine. Melamine is simultaneously embedded in the coating, laying the foundation for subsequent gradient heat treatment and full expansion and foaming under combustion conditions, so that the coating forms a continuous expanded char layer with heat insulation and oxygen barrier function when exposed to fire.
[0013] Preferably, in step S2, the number of alternating immersion cycles is 5 to 20, and the immersion time for each cycle is 3 to 10 minutes.
[0014] By adopting the above technical solution, the deposition amount and film thickness of the flame-retardant polyelectrolyte inner layer are effectively controlled by controlling the number of alternating impregnation cycles and the single impregnation time, so that the coating forms a continuous and uniform coating on the fiber surface, avoiding poor flame retardant efficiency due to insufficient load or stiffness and reduced air permeability due to excessive load; appropriate cyclic deposition ensures sufficient enrichment of phosphorus, nitrogen and metal ion flame retardant components on the fiber surface, providing a structurally regular interface with abundant active sites for subsequent cross-linking fixation and antistatic outer layer lamination assembly.
[0015] Preferably, in step S3, the crosslinking agent solution is a genipin aqueous solution or a citric acid / sodium hypophosphite aqueous solution with a concentration of 2-5 wt%; the crosslinking reaction temperature is 40-60°C and the time is 20-40 min.
[0016] By adopting the above technical solution, the crosslinking agent molecules simultaneously undergo covalent reactions with the primary amine groups on the polyethyleneimine chain, the amino groups on the chitosan molecules, and the hydroxyl or carboxyl groups introduced to the fiber surface by plasma activation under mild conditions, forming a cross-interface chemical crosslinking network between the polyelectrolyte inner layer and the fiber matrix. This covalent anchoring effect firmly locks the layer-by-layer assembled coating, which originally relied on electrostatic bonding, onto the fiber surface, solving the defect of poor washability of traditional layer-by-layer self-assembled coatings, and enabling the flame retardant and antistatic functions to be effectively maintained after multiple washes.
[0017] Preferably, in step S4, the cationic solution is a solution of chitosan dissolved in an aqueous acetic acid solution, with a chitosan concentration of 0.5–1.5 wt%; the anionic solution is an aqueous solution of phytic acid, with a phytic acid concentration of 0.5–2.0 wt%.
[0018] By adopting the above technical solution, chitosan, as a natural cationic polysaccharide, undergoes amino protonation in acidic solution and alternately deposits with anionic phytic acid through electrostatic interaction. Phytic acid molecules contain a large number of phosphate groups, which not only form stable coordination complexes with zinc ions pre-embedded in the polyethyleneimine layer, constructing an ionic cross-linking conductive pathway that runs through the coating, but also, due to its rich phosphorus content, act as a supplementary flame-retardant component, working synergistically with the inner layer expansion system. The introduction of this bio-based outer layer endows the fabric with durable antistatic properties without the use of halogens or organic solvents, while also contributing to the overall flame-retardant effect.
[0019] Preferably, in step S4, the number of alternating immersion cycles is 3 to 8, and the immersion time for each cycle is 3 to 10 minutes.
[0020] By adopting the above technical solution, the number of cyclic assembly and immersion time of the antistatic outer layer are limited to a narrow range, and a bio-based conductive film layer of appropriate thickness is formed on the surface of the flame-retardant inner layer. This not only fully establishes a continuous ion conduction network of chitosan and zinc phytate, reducing the surface resistivity of the fabric and meeting the antistatic workwear standards, but also avoids excessive deposition that could lead to coating thickening and fabric pore blockage, thereby maintaining the original breathability and soft feel of the fabric and meeting the comfort requirements for long-term wear.
[0021] Preferably, in step S4, a nanofiller is added to the cation solution or anion solution, wherein the nanofiller is selected from nano-silica or nano-montmorillonite.
[0022] By adopting the above technical solution, nano-silica or nano-montmorillonite is physically blended and dispersed in a polyelectrolyte solution, and uniformly embedded in the antistatic outer layer during the layer-by-layer self-assembly process. These layered or spherical nanoparticles fill the microscopic defects inside the coating, increase the density and mechanical strength of the coating, and maintain the integrity of the coating structure when subjected to bending, abrasion and washing shear forces. Under combustion conditions, the physical barrier effect of the nanofiller enhances the thermal stability and residual strength of the expanded char layer, making the char layer denser and less prone to cracking, thereby indirectly prolonging the existence time of the antistatic conductive path during combustion and improving the flame-retardant shielding effect.
[0023] Preferably, in step S5, the pre-baking temperature is 80-100℃ and the time is 3-5 min; the baking temperature is 130-160℃ and the time is 2-4 min.
[0024] By adopting the above technical solution, a gradient heat setting process of low-temperature pre-baking followed by high-temperature baking is used to allow moisture in the coating to escape slowly, avoiding shrinkage, cracking, or blistering of the coating caused by instantaneous high temperature. During the baking stage, ammonium polyphosphate and melamine undergo a controlled micro-expansion reaction inside the coating to generate a submicron-level porous structure. This structure increases the interface area for ion conduction, which is beneficial to improving the normal antistatic performance. At the same time, it enables the coating to form a continuous and dense carbon layer with a faster response speed and a more sufficient expansion ratio when it first comes into contact with the flame, effectively protecting the matrix fibers.
[0025] In summary, this application has the following beneficial effects: 1. Because this application constructs an intumescent flame-retardant inner layer containing metal ions and a bio-based antistatic outer layer on the fabric surface, and anchors the entire coating system to the fiber surface through covalent cross-linking, the phosphorus and nitrogen components in the flame-retardant inner layer form a condensed phase with metal ions to synergistically retard the flame-retardant effect, and the antistatic outer layer utilizes the hygroscopic properties of chitosan and the complexation network of phytate and metal ions to establish an ion conduction pathway, thus obtaining a workwear fabric with long-lasting flame-retardant and antistatic functions.
[0026] 2. In this application, a combination of plasma activation pretreatment and covalent anchoring of crosslinking agent is preferred. The oxygen-containing active groups introduced on the fiber surface by plasma activation provide chemical bonding sites for crosslinking agent. The crosslinking agent forms a cross-interface covalent crosslinking network between the polyelectrolyte inner layer and the fiber matrix, thus obtaining a durable protective effect that can withstand multiple washes.
[0027] 3. The method of this application involves pre-complexing zinc ions in a polyethyleneimine solution to allow them to be deposited synchronously with the flame-retardant inner layer. The zinc ions catalyze the char formation reaction in the condensed phase to improve the flame-retardant efficiency and form an ion cross-linked conductive network when in contact with phytic acid. Thus, a single metal ion component is obtained that simultaneously serves as a flame-retardant catalyst and an antistatic conductive agent, avoiding mutual interference between multiple functional additives.
[0028] 4. The method of this application assembles a bio-based antistatic outer layer composed of chitosan and phytic acid on a flame-retardant inner layer by alternating impregnation. The hygroscopic and conductive mechanism of chitosan and the ion conduction mechanism of zinc phytate work synergistically. At the same time, the bio-based outer layer enhances the flame-retardant effect without introducing halogens or organic solvents, thus obtaining a stable electrostatic dissipation capacity and taking into account the synergistic improvement of environmental protection, antistatic performance and flame-retardant performance. Attached Figure Description
[0029] Figure 1 This is a flowchart of the flame-retardant and antistatic composite treatment method for the functional workwear fabric proposed in this application. Detailed Implementation
[0030] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0031] Technical concept: Related textile processing involves finishing processes such as impregnation with flame retardants, coating with conductive polymers, or adding hygroscopic antistatic agents to impart flame retardant or antistatic properties to fabrics. However, this step-by-step process of adding single functions results in a distinct physical interface and poor chemical compatibility between the flame retardant layer and the antistatic layer. Furthermore, halogenated flame retardants and ionic antistatic agents are prone to migration and mutual dilution in hot and humid environments, leading to insufficient adhesion of the coating system. After repeated washing and mechanical friction, the function deteriorates, making it difficult for flame retardant and antistatic properties to coexist stably on the same fabric. This restricts the long-term protective capability of workwear fabrics under complex working conditions such as oil stains, dust, and electric arcs.
[0032] This application discloses a method for flame-retardant and antistatic composite treatment of functional workwear fabrics. The method includes the following steps: S1, plasma activation treatment of the fabric base to obtain a surface-activated fabric; S2, alternating immersion of the surface-activated fabric in cationic polyelectrolyte solution and anionic polyelectrolyte solution to obtain an inner layer deposited fabric; S3, immersion of the inner layer deposited fabric in a crosslinking agent solution to obtain a crosslinked and fixed fabric; S4, alternating immersion of the crosslinked and fixed fabric in cationic and anionic solutions for self-assembly, followed by water washing, to obtain a composite coated fabric; S5, sequential pre-baking and baking of the composite coated fabric to obtain the functional workwear fabric.
[0033] This application constructs an intumescent flame-retardant inner layer containing metal ions and a bio-based antistatic outer layer on the fabric surface, and anchors the entire coating system to the fiber surface through covalent cross-linking. The phosphorus and nitrogen components in the flame-retardant inner layer form a condensed phase with the metal ions to achieve a synergistic flame-retardant effect. The antistatic outer layer utilizes the hygroscopic properties of chitosan and the complexation network between phytate and metal ions to establish an ion conduction pathway, thus obtaining a workwear fabric with long-lasting flame-retardant and antistatic functions.
[0034] Example 1: This example provides a flame-retardant and antistatic composite treatment method for functional workwear fabrics, comprising the following steps: S1. The fabric base is subjected to plasma activation treatment to obtain surface-activated fabric; The plasma activation treatment was performed in an oxygen atmosphere with a power of 50W for 1 minute; the base fabric was a polyester-cotton blend.
[0035] S2. The surface-activated fabric is alternately immersed in cationic polyelectrolyte solution and anionic polyelectrolyte solution for self-assembly. After washing with water in between, an intumescent flame-retardant polyelectrolyte inner layer containing metal ions is formed, resulting in fabric with inner layer deposition. The cationic polyelectrolyte solution is prepared by dissolving polyethyleneimine with a molecular weight of 600 kDa in water to prepare a solution with a concentration of 0.5 wt%, then adding zinc nitrate to make the zinc ion concentration 0.05 mol / L, and stirring to form a complex. The anionic polyelectrolyte solution is prepared by dissolving ammonium polyphosphate with a degree of polymerization of 1000 in water to prepare a solution with a concentration of 1.0 wt%, then adding melamine as an auxiliary char-forming agent to make its concentration 0.2 wt%, and adjusting the pH to 5. The alternating impregnation cycle is 5 times, and the impregnation time is 3 minutes each time.
[0036] S3. Immerse the inner layer of deposited fabric in a crosslinking agent solution to carry out a crosslinking reaction, so that a covalent bond is formed between the flame-retardant polyelectrolyte inner layer and the fabric fibers, and a crosslinked fixed fabric is obtained. The crosslinking agent solution was a genipin aqueous solution with a concentration of 2 wt%; the crosslinking reaction temperature was 40℃ and the time was 20 min.
[0037] S4. The cross-linked fixed fabric is alternately immersed in cationic and anionic solutions to perform self-assembly. After washing with water in between, a bio-based antistatic outer layer is formed on the surface of the flame-retardant polyelectrolyte inner layer to obtain a composite coated fabric. The cationic solution was a solution of chitosan dissolved in an aqueous acetic acid solution with a chitosan concentration of 0.5 wt%; the anionic solution was an aqueous phytic acid solution with a phytic acid concentration of 0.5 wt%; the alternating immersion cycle was 3 times, with each immersion time being 3 minutes; no nanofillers were added to either the cationic or anionic solution.
[0038] S5. The composite coated fabric is pre-baked and baked in sequence to obtain the functional workwear fabric. The pre-drying temperature was 80℃ for 3 minutes, and the baking temperature was 130℃ for 2 minutes.
[0039] Example 2: This example provides a flame-retardant and antistatic composite treatment method for functional workwear fabrics, comprising the following steps: S1. The fabric base is subjected to plasma activation treatment to obtain surface-activated fabric; The plasma activation treatment was performed in an air atmosphere with a power of 125W for 5.5 minutes; the base fabric was a flame-retardant fiber fabric.
[0040] S2. The surface-activated fabric is alternately immersed in cationic polyelectrolyte solution and anionic polyelectrolyte solution for self-assembly. After washing with water in between, an intumescent flame-retardant polyelectrolyte inner layer containing metal ions is formed, resulting in fabric with inner layer deposition. The cationic polyelectrolyte solution is prepared by dissolving polyethyleneimine with a molecular weight of 675 kDa in water to prepare a solution with a concentration of 1.25 wt%, then adding zinc nitrate to make the zinc ion concentration 0.275 mol / L, and stirring to form a complex. The anionic polyelectrolyte solution is prepared by dissolving ammonium polyphosphate with a degree of polymerization greater than 1000 in water to prepare a solution with a concentration of 2.0 wt%, then adding melamine as an auxiliary char-forming agent to make its concentration 0.5 wt%, and adjusting the pH to 6. The alternating impregnation cycle is 12 times, and the impregnation time is 6.5 min each time.
[0041] S3. Immerse the inner layer of deposited fabric in a crosslinking agent solution to carry out a crosslinking reaction, so that a covalent bond is formed between the flame-retardant polyelectrolyte inner layer and the fabric fibers, and a crosslinked fixed fabric is obtained. The crosslinking agent solution was a citric acid / sodium hypophosphite aqueous solution with a concentration of 3.5 wt%; the crosslinking reaction temperature was 50℃ and the time was 30 min.
[0042] S4. The cross-linked fixed fabric is alternately immersed in cationic and anionic solutions to perform self-assembly. After washing with water in between, a bio-based antistatic outer layer is formed on the surface of the flame-retardant polyelectrolyte inner layer to obtain a composite coated fabric. The cationic solution is a solution of chitosan dissolved in an aqueous acetic acid solution with a chitosan concentration of 1.0 wt%; the anionic solution is an aqueous solution of phytic acid with a phytic acid concentration of 1.25 wt%; the alternating impregnation cycle is 5 times, and the impregnation time for each cycle is 6.5 min; the cationic or anionic solution also contains nanofillers selected from nano-silica.
[0043] S5. The composite coated fabric is pre-baked and baked in sequence to obtain the functional workwear fabric. The pre-drying temperature was 90℃ for 4 minutes, and the baking temperature was 145℃ for 3 minutes.
[0044] Example 3: This example provides a flame-retardant and antistatic composite treatment method for functional workwear fabrics, comprising the following steps: S1. The fabric base is subjected to plasma activation treatment to obtain surface-activated fabric; The plasma activation treatment was performed in an air atmosphere with a power of 200W for 10 minutes; the base fabric was a flame-retardant fiber fabric.
[0045] S2. The surface-activated fabric is alternately immersed in cationic polyelectrolyte solution and anionic polyelectrolyte solution for self-assembly. After washing with water in between, an intumescent flame-retardant polyelectrolyte inner layer containing metal ions is formed, resulting in fabric with inner layer deposition. The cationic polyelectrolyte solution is prepared by dissolving polyethyleneimine with a molecular weight of 750 kDa in water to prepare a solution with a concentration of 2.0 wt%, then adding zinc nitrate to make the zinc ion concentration 0.5 mol / L, and stirring to form a complex. The anionic polyelectrolyte solution is prepared by dissolving ammonium polyphosphate with a degree of polymerization greater than 1000 in water to prepare a solution with a concentration of 3.0 wt%, then adding melamine as an auxiliary char-forming agent to make its concentration 0.8 wt%, and adjusting the pH to 7. The alternating impregnation cycle is 20 times, and the impregnation time is 10 min each time.
[0046] S3. Immerse the inner layer of deposited fabric in a crosslinking agent solution to carry out a crosslinking reaction, so that a covalent bond is formed between the flame-retardant polyelectrolyte inner layer and the fabric fibers, and a crosslinked fixed fabric is obtained. The crosslinking agent solution was a citric acid / sodium hypophosphite aqueous solution with a concentration of 5 wt%; the crosslinking reaction temperature was 60℃ and the time was 40 min.
[0047] S4. The cross-linked fixed fabric is alternately immersed in cationic and anionic solutions to perform self-assembly. After washing with water in between, a bio-based antistatic outer layer is formed on the surface of the flame-retardant polyelectrolyte inner layer to obtain a composite coated fabric. The cationic solution is a solution of chitosan dissolved in an aqueous acetic acid solution with a chitosan concentration of 1.5 wt%; the anionic solution is an aqueous solution of phytic acid with a phytic acid concentration of 2.0 wt%; the alternating immersion cycle is 8 times, and the immersion time for each cycle is 10 min; the cationic or anionic solution also contains nanofillers selected from nano-montmorillonite.
[0048] S5. The composite coated fabric is pre-baked and baked in sequence to obtain the functional workwear fabric. The pre-drying temperature was 100℃ for 5 minutes, and the baking temperature was 160℃ for 4 minutes.
[0049] Comparative Example 1: This comparative example refers to the content of Example 1, except that the plasma activation power in step S1 is 20W, and the rest is the same as Example 1.
[0050] Comparative Example 2: This comparative example refers to the content of Example 1, except that the number of cycles of alternating immersion in step S2 is 2, and the rest is the same as Example 1.
[0051] Comparative Example 3: This comparative example is based on the content of Example 2, except that the crosslinking agent solution in step S3 is an aqueous solution of butanetetracarboxylic acid with a concentration of 3.5 wt%. The rest of the content is the same as in Example 2.
[0052] Comparative Example 4: This comparative example refers to the content of Example 2, except that the number of cycles of alternating immersion in step S4 is 1, and the rest is the same as Example 2.
[0053] Comparative Example 5: This comparative example refers to the content of Example 3, except that the baking temperature in step S5 is 110°C, and the rest is the same as Example 3.
[0054] Comparative Example 6: This comparative example is the same as that in Example 3, except that zinc nitrate was not added to the cationic polyelectrolyte solution in step S2. The rest of the contents are the same as those in Example 3.
[0055] Performance testing Sample Preparation: Following the process parameters and treatment conditions described in the examples and comparative examples, the corresponding fabric bases were subjected to flame-retardant and antistatic composite treatments to obtain functional workwear fabric samples for each example and comparative example. All samples were equilibrated for 24 hours under standard atmospheric conditions of 20°C and 65% relative humidity before testing. To examine the wash resistance durability of the finished function, samples of the same specifications were cut from each example and comparative example sample and subjected to 50 household washing cycles according to the washing procedure specified in GB / T8629 standard. After washing, the samples were naturally air-dried to obtain the corresponding wash resistance test samples.
[0056] Flame retardant performance testing procedure: Take the original samples of each example and comparative example, as well as the wash resistance test samples after 50 washes. Cut the samples to 300mm x 80mm size according to GB / T5455 Textiles Vertical Direction Test Method for Burning Performance of Specimens, and place them at 20℃ and 65% relative humidity for 8 hours. During the test, suspend the samples vertically in the combustion test chamber and ignite the center of the bottom edge of the sample using a standard flame at a specified height for 12 seconds. Record the afterflame time and smoldering time of the sample, and measure the charred damage length. At least 3 samples should be tested for each group of samples, and the average value should be taken. The flame retardant performance test standard is GB8965.1-2020 Protective Clothing Flame Retardant Clothing, which specifies a Class B requirement of afterflame time not exceeding 2 seconds, smoldering time not exceeding 2 seconds, and damage length not exceeding 100mm.
[0057] Antistatic performance testing procedure: Take the original samples of each example and comparative example, as well as the wash resistance test samples after 50 washes, and cut them into 60mm x 80mm specimens according to GB / T12703.1 Evaluation of electrostatic properties of textiles - Part 1: Electrostatic voltage half-life test method. The test is conducted under constant temperature and humidity conditions of 20℃ and 35% relative humidity, and the specimens are equilibrated under this environment for 24 hours. Fix the specimens on the specimen clamp, apply a predetermined voltage to charge the specimens, and record the time required for the electrostatic voltage on the specimen surface to decay from the initial value to half, i.e., the electrostatic half-life. At least 3 specimens are tested for each group of samples, and the average value is taken. The test standard for antistatic performance is the point-to-point resistance of 10^7Ω to 10^11Ω or the half-life of less than 2s specified in GB12014-2019 Protective Clothing - Antistatic Garments.
[0058] Verification Test Procedure for Coating Anchorage Strength and Washability: To verify the contribution of cross-linking anchorage to the washability of the coating in this application, original samples from the examples and comparative examples, as well as samples after 50 washes, were taken and tested using a friction tester according to the dry rubbing procedure in GB / T3920 Textiles - Tests for Color Fastness to Rubbing. Under standard atmospheric conditions, the sample was laid flat on the platform of the friction tester, and a rubbing head wrapped with standard white cotton cloth was used to rub the sample surface back and forth 10 times along a 100mm straight line. The presence of coating flaking material on the white cotton cloth was observed, and the mass change of the sample before and after rubbing was measured. This test, by comparing the mass retention rate before and after rubbing with the differences in coating integrity between the examples and comparative examples after washing, indirectly verifies the effect of covalent cross-linking anchorage.
[0059] Table 1 Performance Comparison Table: Example Conclusion: Combining Examples 1-3 and Comparative Example 1 with Table 1, it can be seen that Comparative Example 1 reduced the plasma activation power to 20W, resulting in insufficient introduction of oxygen-containing active groups onto the fiber surface. This weakened the affinity between the polyelectrolyte coating and the fiber matrix, as well as the number of anchor points for subsequent covalent crosslinking. Consequently, the coating easily peeled off from the fiber surface during washing, and both flame-retardant and antistatic components were lost simultaneously, leading to a deterioration in both flame-retardant and antistatic properties. Examples 1-3, using plasma activation within the parameter range, provided a strong chemical bonding foundation for the coating, achieving a durable and wash-resistant overall protective effect. This indicates that plasma activation is a key pretreatment step for enhancing the interfacial bonding between the coating and the fiber, and achieving long-lasting protection.
[0060] Combining Examples 1-3 and Comparative Example 2 with Table 1, it can be seen that Comparative Example 2 reduced the number of alternating impregnation cycles of the flame-retardant polyelectrolyte inner layer in step S2 to 2. This resulted in insufficient deposition of phosphorus and nitrogen flame-retardant components and metal ions on the fiber surface, failing to form a continuous and sufficiently thick intumescent flame-retardant coating. In the combustion test, the density and coverage integrity of the intumescent char layer decreased, resulting in ineffective heat and oxygen insulation, prolonged afterflame time and smoldering time, and a significantly increased damage length. The number of cycles in Examples 1-3 was within the parameter range, ensuring sufficient enrichment and uniform coating of the flame-retardant components, thereby achieving self-extinguishing properties and a low damage length. This indicates that the number of cycles for assembling the flame-retardant inner layer is a factor determining the quality and flame-retardant effect of the intumescent char layer.
[0061] Based on Examples 1-3 and Comparative Example 3, and in conjunction with Table 1, it can be seen that Comparative Example 3, which uses an aqueous solution of butanetetracarboxylic acid to replace the genipin or citric acid / sodium hypophosphite crosslinking system defined in this application, exhibits insufficient reactivity and crosslinking efficiency between the crosslinking agent and the primary amine groups of polyethyleneimine, as well as the active groups on the fiber surface, failing to form a stable covalent crosslinking network across the interface. After washing, the coating peels off, the friction mass retention rate decreases, and the flame retardant and antistatic properties subsequently deteriorate. Examples 1-3, using the defined crosslinking agent system, achieve covalent anchoring of the coating and fiber under mild conditions, indicating that the type of crosslinking agent selected in this application is a guarantee for achieving the long-lasting wash-resistant function of the coating.
[0062] Combining Examples 1-3 and Comparative Example 4 with Table 1, it can be seen that Comparative Example 4 reduced the number of alternating impregnation cycles of the bio-based antistatic outer layer in step S4 to 1. The amount of chitosan and phytic acid deposited was insufficient to form a continuous ion-conducting network, and the complexation pathway between phytic acid and zinc ions was sparse, resulting in a prolonged electrostatic half-life and the antistatic performance not meeting the standard requirements. The number of cycles in Examples 1-3 ensured the construction of the chitosan and phytic acid zinc conductive network, taking into account both electrostatic dissipation capacity and coating thinness, indicating that the antistatic outer layer needs a sufficient number of assembly cycles to establish an effective ion conduction pathway.
[0063] Combining Examples 1-3 and Comparative Example 5 with Table 1, it can be seen that in Comparative Example 5, when the baking temperature was reduced to 110℃, ammonium polyphosphate and melamine failed to undergo sufficient micro-expansion reaction inside the coating, and the coating failed to form a submicron-level porous structure. The ion conduction interface area was small, limiting the normal antistatic performance. At the same time, the pre-activation degree of the char layer precursor was insufficient, and the flame retardant performance was also affected. In Examples 1-3, the baking temperature was within the limited range, and the micro-expansion reaction inside the coating was sufficient. This not only increased the ion conduction pathway but also enabled the coating to quickly form a dense expanded char layer when exposed to fire. This indicates that the baking temperature plays a role in the regulation of the coating microstructure and the synergistic improvement of flame retardant and antistatic performance.
[0064] Combining Examples 1-3 and Comparative Example 6 with Table 1, it can be seen that Comparative Example 6 did not add zinc nitrate to the cationic polyelectrolyte solution, resulting in a lack of zinc ions in the coating system. Consequently, the flame-retardant inner layer lacked the catalytic effect of metal ions on the phosphorylation reaction during combustion, leading to reduced char formation efficiency, insufficient char layer density, increased afterflame time and smoldering time, and increased damage length. Simultaneously, the antistatic outer layer, lacking zinc ions, could not form a phytate-zinc ion cross-linked conductive network, resulting in a prolonged electrostatic half-life. In Examples 1-3, zinc ions were pre-complexed in step S2 to allow them to deposit synchronously with the flame-retardant inner layer. Zinc ions simultaneously played a dual role in flame retardancy and antistatic conductivity, indicating that metallic zinc ions are the component connecting the two functions of flame retardancy and antistatic properties.
[0065] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A method for flame-retardant and antistatic composite treatment of functional workwear fabrics, characterized in that, Includes the following steps: S1. The fabric base is subjected to plasma activation treatment to obtain surface-activated fabric; S2. The surface-activated fabric is alternately immersed in cationic polyelectrolyte solution and anionic polyelectrolyte solution for self-assembly. After washing with water in between, an intumescent flame-retardant polyelectrolyte inner layer containing metal ions is formed, resulting in fabric with inner layer deposition. S3. The inner layer of deposited fabric is immersed in a crosslinking agent solution to carry out a crosslinking reaction, so that the flame-retardant polyelectrolyte inner layer and the fabric fibers form a covalent bond, and a crosslinked fixed fabric is obtained. S4. The cross-linked fixed fabric is alternately immersed in cationic and anionic solutions to perform self-assembly. After washing with water in between, a bio-based antistatic outer layer is formed on the surface of the flame-retardant polyelectrolyte inner layer to obtain a composite coated fabric. S5. The composite coated fabric is pre-baked and baked in sequence to obtain the functional workwear fabric.
2. The flame-retardant and antistatic composite treatment method for functional workwear fabrics according to claim 1, characterized in that, In step S1, the atmosphere for plasma activation treatment is oxygen or air, the treatment power is 50-200W, and the treatment time is 1-10min; the base fabric is a polyester-cotton blended fabric or a flame-retardant fiber fabric.
3. The flame-retardant and antistatic composite treatment method for functional workwear fabrics according to claim 1, characterized in that, In step S2, the cationic polyelectrolyte solution is prepared by dissolving polyethyleneimine with a molecular weight of 600-750 kDa in water to prepare a solution with a concentration of 0.5-2.0 wt%, then adding zinc nitrate to make the zinc ion concentration 0.05-0.5 mol / L, and stirring to complex.
4. The flame-retardant and antistatic composite treatment method for functional workwear fabrics according to claim 1, characterized in that, In step S2, the anionic polyelectrolyte solution is prepared by dissolving ammonium polyphosphate with a degree of polymerization ≥1000 in water to prepare a solution with a concentration of 1.0 to 3.0 wt%, then adding melamine as an auxiliary char-forming agent to make its concentration 0.2 to 0.8 wt%, and adjusting the pH to 5 to 7.
5. The flame-retardant and antistatic composite treatment method for functional workwear fabrics according to claim 1, characterized in that, In step S2, the number of alternating immersion cycles is 5 to 20, and the immersion time for each cycle is 3 to 10 minutes.
6. The flame-retardant and antistatic composite treatment method for functional workwear fabrics according to claim 1, characterized in that, In step S3, the crosslinking agent solution is an aqueous solution of genipin or an aqueous solution of citric acid / sodium hypophosphite, with a concentration of 2-5 wt%; the crosslinking reaction is carried out at a temperature of 40-60°C for 20-40 min.
7. The flame-retardant and antistatic composite treatment method for functional workwear fabrics according to claim 1, characterized in that, In step S4, the cationic solution is a solution of chitosan dissolved in an aqueous acetic acid solution, with a chitosan concentration of 0.5–1.5 wt%; the anionic solution is an aqueous solution of phytic acid, with a phytic acid concentration of 0.5–2.0 wt%.
8. The flame-retardant and antistatic composite treatment method for functional workwear fabrics according to claim 1, characterized in that, In step S4, the number of alternating immersion cycles is 3 to 8, and the immersion time for each cycle is 3 to 10 minutes.
9. The flame-retardant and antistatic composite treatment method for functional workwear fabrics according to claim 1, characterized in that, In step S4, a nanofiller is added to the cation solution or anion solution, the nanofiller being selected from nano-silica or nano-montmorillonite.
10. The method for flame-retardant and antistatic composite treatment of functional workwear fabrics according to claim 1, characterized in that, In step S5, the pre-baking temperature is 80-100℃ and the time is 3-5 min; the baking temperature is 130-160℃ and the time is 2-4 min.